STRATEGI PENGEMBANGAN USAHA BUDIDAYA IKAN NILA (Oreochromis niloticus) DI KECAMATAN MALUA KABUPATEN ENREKANG - Fitriyanti Fitriyanti; Muhammad Bibin; Damis Damis (PAPALELE (Jurnal Penelitian Sosial Ekonomi Perikanan dan Kelautan), 2023)
The potential of natural resources, especially the water system owned by Malua District, is the best potential when compared to other sub-districts in Enrekang district, so it is very possible to manage it optimally. This study aims: (1) to determine the conditions of tilapia aquaculture at the research site, (2) to analyze the costs and income of freshwater fish cultivators at the research site, and (3) to determine the strategy for developing tilapia aquaculture business at the research location. This research was carried out for 2 (two) months, namely in December 2022 - February 2023 to be precise in Malua District, Enrekang Regency. The types of data used are primary data and secondary data using survey methods and data collection techniques which include observation, interviews, documentation and literature studies. Data analysis used is quantitative descriptive analysis. The results of this study indicate that the condition of fisheries in Malua District has not carried out a cultivation process that is in accordance with existing cultivation standards, especially in the number of seed stockings that are not in accordance with the area of ​​the rearing ponds and the dosage of feeding. The costs for tilapia aquaculture are fixed costs per cycle of Rp 218.411 and annually Rp 436.823, per cycle variable cost of Rp 3.118.874 and annually Rp 6.237.748, - and for operational costs per cycle Rp 3.337.285, - and for a year Rp 6.674.570, -. The average gross income of fish cultivators per cycle is Rp 9.300.000, - and annually Rp 18.600.000, - while the average net income (profit) obtained by cultivators per cycle is Rp 5.962.715 and for a year it is Rp 11.925.430.